MOVING FROM THEORY TO PRACTICE: A SYSTEMATIC REVIEW ON ESTABLISHING CRITICAL LITERACY IN EFL SETTINGS - Hanif Nurcholish Adiantika; Emi Emilia; Gin Gin Gustine (University of Kuningan, 2025)
Research in critical literacy has conventionally put an emphasis on English as a second language contexts, with limited exploration in environments of English as a foreign language (EFL) where English is seldom utilized outside of the classroom. This study aims to scrutinize the incorporation of critical literacy within the context of Teaching English to Speakers of Other Languages (TESOL), a domain that has been disregarded by TESOL scholars and practitioners in EFL contexts. This study assesses and integrates existing literature through delineating the theoretical framework of critical literacy in TESOL, demonstrating instances of its implementation, and deliberating on the advantages and shortcomings linked with integrating critical literacy into teaching practices. Ultimately, the present study advocates for further investigation into critical literacy in EFL contexts.